Stem cell‐derived extracellular vesicles mitigate ageing‐associated arterial stiffness and hypertension. Issue 1 (24th June 2020) - Feng, Rui; Ullah, Mujib; Chen, Kai; Ali, Quaisar; Lin, Yi; Sun, Zhongjie
ABSTRACT: The prevalence of arterial stiffness and hypertension increases with age. This study investigates the effect of induced pluripotent mesenchymal stem cell‐derived extracellular vesicles (EVs) on ageing‐associated arterial stiffness and hypertension. EVs were collected and purified from induced pluripotent stem cell‐derived mesenchymal stem cells (iPS‐MSCs). Young and old male C57BL/6 mice were used. Mice in the EVs group were injected via tail vein once a week for four weeks (18 x 10 6 EVs/mouse/injection). Blood pressure (BP) was measured using the tail‐cuff method and validated by direct cannulation. Pulse wave velocity (PWV) was measured using a Doppler workstation. PWV and BP were increased significantly in the old mice, indicating arterial stiffness and hypertension. Intravenous administration of EVs significantly attenuated ageing‐related arterial stiffness and hypertension, while enhancing endothelium‐dependent vascular relaxation and arterial compliance in the old EVs mice. Elastin degradation and collagen I deposition (fibrosis) were increased in aortas of the old mice, but EVs substantially improved ageing‐associated structural remodelling. Mechanistically, EVs abolished downregulation of sirtuin type 1 (SIRT1), and endothelial nitric oxide synthase (eNOS) protein expression in aortas of the older mice. In cultured human aortic endothelial cells, EVs promoted the expression of SIRT1, AMP‐activated protein kinase alpha (AMPKα), and eNOS. In conclusion, iPS‐MSC‐derived EVs attenuated ageing‐associated vascular endothelial dysfunction, arterial stiffness, and hypertension, likely via activation of the SIRT1‐AMPKα‐eNOS pathway and inhibition of MMPs and elastase. Thus, EVs mitigate arterial ageing. This finding also sheds light into the therapeutic potential of EVs for ageing‐related vascular diseases. Abbreviations: EV: Extracellular vesicles; iPS: induced pluripotent stem cell; MSC: mesenchymal stem cell; AMPKα: AMP activated protein kinase α; eNOS: endothelial nitric oxide synthase; Sirt1: sirtuin 1; JNC7: Seventh Report of the Joint National Committee; CVD: cardiovascular disease; PWV: pulse wave velocity; BP: blood pressure; SNP: sodium nitroprusside